Evaluación de la calidad de obturación de los conductos radiculares realizados por los alumnos de pregrado de la carrera de Odontología de una Universidad Privada de Lima - Perú- en el año 2013 - La Rocca Chiape, Flavia (2014)
Objective: To evaluate the quality of root canal filling performed by undergraduate students in dental school at a private university in Lima, during the period 2011-2013. Methods: We performed a compilation of all periapical radiographs of patients with root canal treatment performed by undergraduate students of a private college of Dentistry in Lima, in the period 2011-2013 according to the selection criteria. The sample consisted of 501 root canals evaluated radiographically. We assessed the quality of the seal from the criteria proposed by Barrieshi-Nusair that measures the length and density of seals and other variables such as the location of the tooth, the gender of the students, clinic studied (course of study) and common mistakes during endodontic treatment. We performed chi-square test to establish the associations of the study variables. Results: With regard to quality, it was found that the canals evaluated had a 62,67% acceptable quality. It was also found that 79.44% had acceptable sealing length and 74.45% had acceptable density. We found a statistically significant association between the location of the piece with the length of the root canal filling (p=0.005), and the density of the root canal filling (p=0,005). There was also found a relationship between the clinic studied with the length of the root canal filling (p=0.019) and the filling density (p=0.021). There was no association between gender of the student with the filling density (p=0.347) and the length of the filling (p=0.269). There was a low error rate (4%) in the treatments done. Conclusions: The length and density of the filling was acceptable in most cases. Statistically significant associations were found between the location of the piece and the clinic studied in relation to length and density of the filling.